Effects of Bacillus subtilis, butyrate, mannan-oligosaccharide, and naked oat (ß-glucans) on growth performance, serum parameters, and gut health of broiler chickens - A. Rouissi (Elsevier, 2021)
ABSTRACT: Four nonantibiotic alternative growth promoters for broiler chickens were evaluated. Ross 308 chicks were fed a control diet (mainly corn and soybean meal) or a diet supplemented with a probiotic (Bacillus subtilis Gallipro DSM 17299), encapsulated butyric acid (Novyrate C), mannan-oligosaccharide (Actigen MOS) or formulated with 20% naked oat (starter diet) and 30% naked oat (grower and finisher). The study was carried out as a complete random blocked design with 10 pens for each diet, 45 birds per pen. Compared to the control, the naked oat diet improved the average daily gain by 16% during the starter phase (up to d 10). The probiotic did so during the grower phase as did butyric acid in the finisher phase (up to d 34). For the experiment overall, the probiotic decreased average daily gain slightly. The best improvement in feed conversion ratio was obtained in the butyrate group (5%). No significant treatment effect on crop pH or on mortality was observed. The naked oat diet gave a slightly lower cecum pH on d 34. The MOS supplement decreased jejunal mass on d 34 and increased villus length (34%) and villus height/crypt depth ratio (32%) measured on d 10. Naked oat, butyric acid and MOS diets all reduced serum endotoxin levels. The probiotic increased serum C-reactive protein. All noncontrol diets reduced serum malondialdehyde. The naked oat diet reduced d 34 litter pH by about 0.3. Some effects of the proposed non-antibiotic growth promoters have been observed and could contribute to livestock performance. Their exact modes of action remained to be defined.